2008
DOI: 10.1016/j.jfms.2008.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of risk factors for cat mortality in adoption centres of a UK cat charity

Abstract: A case-control study was used to identify variables associated with the risk of mortality in cats housed at adoption centres. Multivariable logistic regression, based on retrospective data collected for 194 cases (cats that died or were euthanased) and 320 controls (cats that did not die) revealed an increased risk of mortality for cats admitted to adoption centres unneutered, in fair/poor health and cats born at adoption centres. Cats aged 7 weeks or less and cats aged over 7 years had an increased risk of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…The health status of each cat should be assessed objectively, preferably by a veterinarian at the time of admission. Murray et al (2008) found an increased risk of mortality in cats admitted to adoption centres in poor health. The medical records of 364 kittens taken into PAWS Chicago Adoption Centre in 2008 showed that only 104 (28.5%) had no abnormalities identified in a physical examination performed by the shelter veterinarian at the time of intake (Litster et al 2011).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The health status of each cat should be assessed objectively, preferably by a veterinarian at the time of admission. Murray et al (2008) found an increased risk of mortality in cats admitted to adoption centres in poor health. The medical records of 364 kittens taken into PAWS Chicago Adoption Centre in 2008 showed that only 104 (28.5%) had no abnormalities identified in a physical examination performed by the shelter veterinarian at the time of intake (Litster et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Our results are in agreement with the results of a study analyzing the risk of mortality in cats kept at the adoption centres of a UK cat charity. Murray et al (2008) reported that the risk of mortality decreased as the time in the adoption centre increased. The increasing risk of contracting an infection for cats staying longer in shelters found in other studies (Pedersen et al 2004;Dinnage et al 2009) did not seem to affect the mortality rate in the shelters monitored in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations